DIALEKTIKA ANTARA TRADISI ADAT MALUKU DAN SYARIAT ISLAM PASCA TRAGEDI KEMANUSIAN 1999 - Jamilu, La; Humaidi, Anis (Universitas Islam Negeri Sunan Ampel, 2026)
The 1999 humanitarian conflict in Maluku not only triggered large-scale religious violence but also disrupted the traditional social and cultural order that had long sustained communal harmony. In the post-conflict context, Maluku society demonstrates a distinctive dynamic through the revitalization of customary traditions and the strengthening of local Islam as foundations for social reconciliation. This article aims to analyze the dialectical relationship between Maluku customary traditions and Islamic law in the aftermath of the 1999 conflict using the Functional Integration theory. Employing a qualitative descriptive approach, this study is based on a systematic literature review of peer-reviewed journals, books, and scholarly publications from the last five years (2020–2025). The findings reveal that customary law and Islamic law in Maluku are not antagonistic but functionally integrated, fulfilling complementary social, moral, and spiritual roles. Local Islam provides ethical and religious legitimacy for peacebuilding, while the Pela Gandong customary system serves as a cross-religious mechanism of social cohesion. This functional integration significantly contributes to post-conflict reconciliation, the strengthening of religious moderation, and the reconstruction of contextual and peaceful Islamic identity in Maluku.